Chiral defects on single-handed helical Ta2O5 nanotubes prepared using a supramolecular templating approach1. Issue 73 (9th August 2015) - Zhang, Chuanyong; Wang, Yong; Qin, Jiaming; Li, Baozong; Li, Yi; Yang, Yonggang
<x xml:space="preserve">Abstract</x> Chiral point defects were responsible for the optical chirality of the single-handed helical Ta2O5 nanotubes prepared using a supramolecular templating approach.